2002
DOI: 10.1038/sj.bjc.6600438
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomal abnormalities, multipolar mitoses, and chromosomal instability in head and neck tumours with dysfunctional telomeres

Abstract: Carcinomas of the head and neck typically exhibit complex chromosome aberrations but the underlying mutational mechanisms remain obscure. Evaluation of cell division dynamics in low-passage cell lines from three benign and five malignant head and neck tumours revealed a strong positive correlation between multipolarity of the mitotic spindle and the formation of bridges at anaphase in both benign and malignant tumours. Cells exhibiting a high rate of mitotic abnormalities also showed several chromosome termini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
2
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 31 publications
3
74
2
2
Order By: Relevance
“…Furthermore, all MMs that were analyzed by immunofluorescence in the present study showed two or more centrosomes. The frequencies of AB and MM are positively correlated in many types of neoplasia (20,34,35). In the present study, MM was never present in the cultured WT cells or tissue sections without AB being present as well.…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, all MMs that were analyzed by immunofluorescence in the present study showed two or more centrosomes. The frequencies of AB and MM are positively correlated in many types of neoplasia (20,34,35). In the present study, MM was never present in the cultured WT cells or tissue sections without AB being present as well.…”
Section: Discussioncontrasting
confidence: 47%
“…Telomere shortening has been demonstrated to contribute directly to the presence of chromosomal abnormalities usually found in diverse types of cancer. This telomere reduction may trigger the formation of telomeric fusions between chromosome arms, which may result in novel karyotypic rearrangements (32,33). Different reports showed similar genetic alterations in MGUS and MM, which suggests a model for MGUS evolution based on genomic instability manifested by aneuploidy as the permissive event for the occurrence of chromosome alterations (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The concurrence of telomere dysfunction and centrosome amplification plays an important role in the generation of chromosomal abnormalities that are characteristically found in neoplasia, but the mechanistic link of these two distinct cellular events is still unclear. Recently, Gisselsson proposes a hypothesis that focused on this question after analysis of a series of genetic alterations in various kinds of human cancers (Gisselsson et al, 2002(Gisselsson et al, , 2004Gisselsson, 2005). According to his concept, telomeric erosion can initially induce chromosomal bridging secondary to telomeric fusion in anaphase with resultant failure in cytokinesis, giving rise to cells with supernumerary centrosomes, which consequently leads to numerical chromosomal aberrations by causing multipolar divisions.…”
Section: Discussionmentioning
confidence: 99%